PENGARUH BRAND LOVE, CUSTOMER TRUST DAN BRAND IMAGE TERHADAP LOYALITAS PELANGGAN MS GLOW - Devi Fitri Arianti; Onsardi Onsardi (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2025)
This study aims to determine the influence of Brand Love, Customer Trust, and Brand Image on MS Glow Customer Loyalty. The case study focuses on users of MS Glow products in Pasar Kepahiang Sub-district, Kepahiang Regency. This research is a descriptive quantitative study, with the population being MS Glow product users in the area. The sampling method used is proportional sampling, with a total of 140 respondents. Data collection was carried out using a questionnaire. Data analysis techniques included multiple linear regression analysis, coefficient of determination analysis, and hypothesis testing. Based on the data processing results using SPSS 25, the regression equation obtained is: Y2.761+0.162 X1 +0.191 X2+0.309 X3 ei with an R Square (R³) value of 0.366, meaning that the independent variables contribute 36.6% in influencing the dependent variable. The hypothesis test results show that Brand Love, Customer Trust, and Brand Image collectively have a positive and significant effect on Customer Loyalty. Keywords: Brand Love, Customer Trust, Brand Image, and Customer Loyalty.